Effect of Profit and Cash Flow in Prediction of Financial Distress Conditions - Krisna Trizelika Wahyuni; Leriza Desitama Anggraini; Andini Utari Putri (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to examine the effect of earnings and cash flow on the prediction of financial distress. Profit and cash flow as independent variables and finance as the dependent variable. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The sampling technique in this study used purposive sampling. The samples in this study were 18 consumer and manufacturing goods companies listed on the stock exchange. The analytical method used is multiple linear regression. This research shows that profit has a significant effect on financial distress. While cash flow has a significant effect on financial distress. This result is explained by the simultaneous test (F test) the significant value is greater than the significant level of 0.05 or 0.000 <0.05. This means that it is certain that profit and cash flow have the ability to influence financial distress